2014
DOI: 10.1002/eji.201344399
|View full text |Cite
|
Sign up to set email alerts
|

iNKT‐cell help to B cells: A cooperative job between innate and adaptive immune responses

Abstract: T-cell help to B lymphocytes is one of the most important events in adaptive immune responses in health and disease. It is generally delivered by cognate CD4 + T follicular helper (T FH ) cells via both cell-to-cell contacts and soluble mediators, and it is essential for both the clonal expansion of antibody (Ab)-secreting B cells and memory B-cell formation. CD1d-restricted invariant natural killer T (iNKT) cells are a subset of innate-like T lymphocytes that rapidly respond to stimulation with specific lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 69 publications
(149 reference statements)
1
22
0
Order By: Relevance
“…However, it remains to be determined whether the B memory responses elicited by type II NKT cells are short lived, as seen in the case of type I NKT T FH . 8 These results are of great interest, as the authors report an increased frequency of LGL1-specific T cells in a mouse model of GD and in patients with GD (over 20-fold in mice and 3-fold in humans). Notably, the frequency of type I NKT in GD mice is significantly reduced, in agreement with data showing impairment in their selection in mouse models of lysosomal storage disorders.…”
Section: Conflict-of-interest Disclosurementioning
confidence: 91%
See 1 more Smart Citation
“…However, it remains to be determined whether the B memory responses elicited by type II NKT cells are short lived, as seen in the case of type I NKT T FH . 8 These results are of great interest, as the authors report an increased frequency of LGL1-specific T cells in a mouse model of GD and in patients with GD (over 20-fold in mice and 3-fold in humans). Notably, the frequency of type I NKT in GD mice is significantly reduced, in agreement with data showing impairment in their selection in mouse models of lysosomal storage disorders.…”
Section: Conflict-of-interest Disclosurementioning
confidence: 91%
“…5 Clinical relapse within several months has been documented after partial response to vemurafenib. 8 How long patients can be maintained after relapse from complete or partial remission before requiring additional therapy has yet to be reported. Thus far, other treatments for HCL that are associated with elimination of HCL MRD include cladribine alone, at least in a minority of cases, purine analogs combined with rituximab in a majority of cases, and the anti-CD22 recombinant immunotoxin moxetumomab pasudotox.…”
mentioning
confidence: 99%
“…iNKT cells mediate their effector function primarily through rapid cytokine release following activation [39], including both Th1 (IFN-γ and TNF-α), Th2 (IL-1, IL-4, and IL-13), and Th17 (IL-17, IL-22) cytokines [38, 41]. They have also been shown to enhance B cell responses through both cognate and noncognate mechanisms [42]. …”
Section: Inkt Cellsmentioning
confidence: 99%
“…Recently, however, it became clear that CD1d-restricted natural killer T (NKT) cells, a subset of lipid-specific T lymphocytes that display innate-effector functions, can also help B cell responses [3]. Both CD4 + T and…”
Section: Cd4mentioning
confidence: 99%
“…Several studies have shown that iNKT cells provide help to B cells, either directly or indirectly, with different outcomes [3]. Therefore, iNKT cells are considered as a bridge between innate and adaptive immune responses.…”
Section: Cd1d-restricted Natural Killer T Cellsmentioning
confidence: 99%